2018
DOI: 10.1002/stem.2910
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Heart-Derived Cell Therapy 2.0: Paracrine Strategies to Increase Therapeutic Repair of Injured Myocardium

Abstract: Despite progress in cardiovascular medicine, the incidence of heart failure is rising and represents a growing challenge. To address this, ex vivo proliferated heart-derived cell products have emerged as a promising investigational cell-treatment option. Despite being originally proposed as a straightforward myocyte replacement strategy, emerging evidence has shown that cell-mediated gains in cardiac function are leveraged on paracrine stimulation of endogenous repair and tissue salvage. In this concise review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…With the astounding number of recent heart stem cell retractions, many have legitimately begun to question what contribution heart-derived (paracrine) therapeutics may ever provide to patient care [8]. To this, a reassuringly large body of work validates the therapeutic use of heart-derived cells but the future role of these cells is uncertain [45]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the astounding number of recent heart stem cell retractions, many have legitimately begun to question what contribution heart-derived (paracrine) therapeutics may ever provide to patient care [8]. To this, a reassuringly large body of work validates the therapeutic use of heart-derived cells but the future role of these cells is uncertain [45]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated that the functional benefit of cardiac cell therapy is due to an acute inflammatory-based wound healing response that rejuvenates the mechanical properties of the infarcted area of the heart. In addition, the heart itself has stem cells, which can slowly selfrenew (Rafatian and Davis, 2018). A radioactive isotope study demonstrated that human cardiomyocytes gradually renew 1% of the cell population annually at the age of 25 years to 0.45% at the age of 75 years, which suggests that the heart has the limited ability of endogenous repair (Bergmann et al, 2009).…”
Section: Mechanism Of Stem Cell Therapymentioning
confidence: 99%
“…Surprisingly, solely injecting the conditioned medium from these stem cells has shown restorative effects on the heart (Alibhai et al, 2018; Bollini et al, 2018). The restorative effects have been attributed to the secretion of paracrine factors, including EVs, from the stem cells (Alibhai et al, 2018; Bollini et al, 2018; Rafatian & Davis, 2018; Saha et al, 2019). Most EV studies in the cardiac area are based on 2D cultures or in vivo models with very few using 3D in vitro culture systems.…”
Section: Extracellular Vesicles From Organoids and 3d Culture Model Smentioning
confidence: 99%